The Islamization of Science and Its Consequences: An Examination of Ismail Raji Al-Faruqi’s Ideas - Sawaluddin, Sawaluddin; Harahap, Koiy Sahbudin; Rido, Imran; Supriono, Iwan Agus (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2022)
This research is motivated by the advancement of science, which has varied effects on human life and the environment. Science, on the one hand, can help and reduce human burdens, but it also contributes to the destruction of human values, and even self-existence. Western science, which is secular in nature, is founded on the concepts of materialism, naturalism, and existentialism, producing information that is divorced from spiritual and moral values. As a result, Islamic scholars believe that the Islamization of science must be formalized. The goal of this research was to learn about Ismail Raji Al-Faruqi’s concept of Islamization of Science. The literature study approach was employed in this study, which involved examining journals, books, research reports, periodicals, and other publications. According to the findings of this study, al-Faruqi is a figure with excellent ideas for resolving people’s issues. The concept of education is inextricably linked to the concept of monotheism, which became known as the Islamization of knowledge. Islamization is accomplished by a process of rationalization and sacralization of knowledge, as well as through the integration of Western and Islamic science. Al-Faruqi’s ideas contribute to the intellectual development of Muslim civilization by integrating Islamic moral standards with modern education, giving rise to intellectuals all over the world, including in Indonesia.